Always learning: how to stay mentally agile and curious in times of change - Wakeham, C (Bodleian Libraries, University of Oxford, 2022)
Whether it is welcome or not, in or out of our control, change is always challenging and always gives us opportunities for learning. It can be confusing, clarifying, worrying, exciting – sometimes all at the same time! What mental ‘tricks’ can we use to cope with change, to ride out the rough spots and learn from it?